Digital Accessibility at the Brazilian Symposium on Human Factors in Computing Systems (IHC): An Updated Systematic Literature Review - Da Costa Nunes, Erik Henrique; Ribeiro, Guilherme Vital; Monteiro, Ingrid Teixeira; Gonçalves, Enyo (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
In 2015, Brazil enacted Law No. 13,146 (Statute of Persons with Disabilities), establishing a new range of rights for people with disabilities. Among the changes made was the inclusion of good practices in the concept of accessibility, including the digital realm. This paper presents the results of a Systematic Literature Review regarding the works presented at the Brazilian Symposium on Human Factors in Computing Systems from 2016 to 2022, with the aim of evaluating the impact of Digital Accessibility initiatives after the enactment of the mentioned law. The objective is to reveal part of the event’s history, highlighting the needs imposed by the law. The study analyzed 406 papers from the event deposited in the ACM Digial Library, selecting 91 of them (22.4%). The results showed that visual impairment is the most addressed theme, present in 33 papers (36.2%). Also, there are 254 different researchers working on this topic in Brazil and other countries. Surprisingly, only 21 (23%) of the papers mention any laws, showing that there is neglect or lack of knowledge regarding Brazilian laws on accessibility.